Internationalization of MSMEs Through Networks (Networking) To Improve Welfare - Zulpardisyah Zulpardisyah (Journal Research of Social Science, Economics, and Management, 2022)
Internationalization of MSMEs through networking in the context of improving welfare must be carried out in stages. To find out the various welfare conditions of MSMEs, several sustainable development systems are needed, so that the standard of living of MSMEs in the country continues to increase. The orientation and focus“on empowering MSMEs that will be internationalized need to be improved, including by providing easy access to company functions and providing supporting facilities, so that all MSMEs that will be internationalized can apply general rules that apply in the economy in a consistent, consistent and efficient manner. The efforts made are through a strong business network (networking). The network is an important factor in the MSME business both on a national and international scale in order to improve welfare, economies of scale, and expand market share. MSMEs with a strong network are the capital to run their business activities effectively and efficiently.